Reproduction, intracapsular development and carryover effect of the Mediterranean gastropod after long-term exposure to low pH - Sanja Gran; Sam Dupont; Luka Glamuzina; Ana Bratoš Cetinić (PANGAEA, 2025)
Spawning performance, intracapsular development and carryover effect of the banded dye murex (Hexaplex trunculus) were investigated following long-term exposure (>250 days) to a range of pHs. Gastropods were collected in Bistrina Bay, part of the Mali Ston Bay in the Southeastern Adriatic Sea (42°52 extquotesingle19.1 N 17°42 extquotesingle02.3 E). Experiment was performed in Laboratory for Mariculture, University of Dubrovnik, located ion the Bistrina Bay. Details of the experiment setting and carbonate chemistry measurements are available in PANAGEA datasets Gran et al. 2024 & Gran et al. 2025. After 250 days of exposure marked females were separated into individual containers. Until the start of spawning, females were fed Mediterranean mussel, Mytilus galloprovincialis. The start and duration of spawning were recorded for each female. The number of females spawning was recorded for each pH treatment. Immediately after spawning, ten randomly selected capsules from each spawn were measured with a digital caliper (precision 0.01 mm) for length (cl, mm), width (cw, mm) and thickness (ct, mm), with the length being the greatest distance between the basal membrane and the apex, width the greatest distance between lateral edges at right angles to length, and thickness the greatest distance from convex side to concave side at right angles to length and width (D extquotesingleAsaro, 1986). Five capsules were carefully opened with a scalpel; eggs were emptied onto a microscope slide and counted under a stereo microscope (Olympus SZ40). The method for monitoring intracapsular development was modified following previous studies by Vasconcelos et al. (2004), Lahbib et al. (2010), and Gűller and Lok (2014). Four days after spawning, a minimum of two capsules were carefully removed from each spawn. Fertilized eggs were emptied onto a microscope slide and photographed with a microscope digital camera (Olympus DP72) under a light microscope (Olympus BX51). The diameter of a minimum of 50 eggs from each capsule was measured with the software Fiji. To determine the stage of intracapsular embryonic development, random capsules were sampled a minimum of four times until hatching. The capsules were preserved in 4% solution of formaldehyde in seawater for further analysis. Each capsule was carefully opened with a scalpel and emptied onto a slide. The embryos were photographed under a light microscope and the length was measured using the Fiji software. The developmental stage was determined based on the characteristic structures. To evaluate the carryover effect of parental exposure on the embryos sensitivity to pH, spawns were transferred to different pHs following the scheme presented in Fig. 1. Spawns were selected based on their size and accessibility. After females completed the spawning, the selected spawns were carefully separated with a scalpel and cut in half. One-half of the spawn was returned to the pHT from which it had been removed, and the other half was placed in the designated pHT. At minimum four times over the course of the intracapsular development, two capsules were carefully removed from transplants and placed in 4% formaldehyde for further analysis (measurement of embryo size and developmental stages). Carbonate Chemistry data were downloaded from the PANGAEA dataset (see Source). In order to allow full comparability with other ocean acidification data sets, the R package seacarb (Gattuso et al, 2024) was used to compute a complete and consistent set of carbonate system variables, as described by Nisumaa et al. (2010). In this dataset the original values were archived in addition with the recalculated parameters (see related PI). The date of carbonate chemistry calculation by seacarb is 2024-02-26.